A comparative single-dose bioequivalence study of two enteric coated Aspirin brands among healthy volunteers. (c2001) - Zeitoun, Abeer Abbas (2001)
(Aspicot®) is an enteric coated aspirin that is being extensively used among patients in the Middle East, including Lebanon where this drug is manufactured, without any clinical in-vivo implication showing or confirming its bioequivalence. Therefore, this investigation was carried out LO evaluate the in-vitro dissolution as well as the bioavailability and pharmacokinetic properties of two tablet oral dosage forms of enteric coated aspirin, Aspirin Protect® (Bayer©, Germany) and Aspicot® (Pharmaline©, Lebanon) in a single dose of 200 mg among healthy volunteers. Method: Twelve healthy volunteers (seven males, five females), were enrolled in the study. Each volunteer received a single dose of each drug in an open randomized two-way crossover study, with a washout period of seven days. Blood samples were obtained at different time intervals over a period of 12 hours. These samples were then analyzed for serum acetylsalicylic acid and salicylic acid levels, using a sensitive HPLC assay. Results: The two products were found to comply with the compendial requirements for both disintegration and content uniformity; and their in -vitro dissolution characteristics were similar. Moreover, there was no statistically significant difference with respect to peak serum concentration (The Cmax values for Aspicot® (23,66 ± 16,26 ~g / mL) and Aspirin Protect® (21.73 ± 11.33 ug / mL) or to corresponding peaks time (the Tmax values ( 4,92 ± 2.35 hours and 4,58 ± 1,5 1 hours for Aspicot® and Aspirin Protect® respectively), Furthermore, the difference between area under the serum concentration time curve for the two products (the AUC for Aspicot® (66,20 ± 42,90 ug / mL) and Aspirin Protect® (64,79 ± 38,02 ug / mL) was not statistically significant, with P > 0,05. Conclusion: The findings in this study indicate that the two products are bioequivalent in terms of bioavailability and pharmacokinetic properties on healthy volunteers.